Action research to improve confidence in meeting diverse need and the quality of inclusive practice through lesson observations. Issue 2 (24th May 2020) - Connett, Helen
Abstract : This paper reports an action research study undertaken towards the National Award for Special Educational Needs Coordination (NASENCO) on a university‐based course. It follows an earlier evaluative study that identified a tension between teachers' self‐rated high levels of confidence in meeting diverse need and values which did not appear to support inclusive practice. The 'action' which was subsequently taken was the collection of further data through lesson observations to assess whether such confidence was reflected in inclusive classroom practice. Planning reviews were also undertaken. Several recognised features of inclusive practice that are known to benefit pupils with special educational needs (SEN) were not observed in all classrooms. The action research study findings identified very specific training needs relating to inclusive classroom practice, the design of individual education plans and the development of a shared school ethos and understanding of inclusive pedagogy.